Nicotinamide Mononucleotide Attenuates Renal Interstitial Fibrosis After AKI by Suppressing Tubular DNA Damage and Senescence - Jia, Yan; Kang, Xin; Tan, Lishan; Ren, Yifei; Qu, Lei; Tang, Jiawei; Liu, Gang; Wang, Suxia; Xiong, Zuying; Yang, Li (Frontiers in Physiology, 2021)
Acute kidney injury (AKI) is a worldwide health problem currently lacking therapeutics that directly promote renal repair or prevent the occurrence of chronic fibrosis. DNA damage is a feature of many forms of kidney injury, and targeting DNA damage and repair might be effective strategies for kidney protection in AKI. Boosting nicotinamide adenine dinucleotide (NAD+) levels is thought to have beneficial effects on DNA damage repair and fibrosis in other organs. However, no kidney-related studies of such effects have been performed to date. Here, we have shown that NMN (an NAD+ precursor) administration could significantly reduce tubular cell DNA damage and subsequent cellular senescence induced by hydrogen peroxide and hypoxia in human proximal tubular cells (HK-2 cells). The DNA damage inhibition, antiaging and antiinflammatory effects of NMN were further confirmed in a unilateral ischemia-reperfusion injury (uIRI) mouse model. Most importantly, the antifibrosis activity of NMN was also shown in ischemic AKI mouse models, regardless of whether NMN was administered in advance or during the recovery phase. Collectively, these results suggest that NMN could significantly inhibit tubular cell DNA damage, senescence and inflammation. NMN administration might be an effective strategy for preventing or treating kidney fibrosis after AKI.